From heterocyclic hydrazone to hydrazone-azomethine dyes: Solvent and pH induced hydrazone and azo-keto transformation for a family of pyrazolone-based heterocyclic dyes. (February 2017) - Geng, Jiao; Xu, Dan; Chang, Fei-Fan; Tao, Tao; Huang, Wei
Abstract: A series of pyrazolone-based full heterocyclic and half heterocyclic hydrazone dyes as well as aniline modified hydrazone-azomethine dyes has been successfully synthesized and spectrally characterized. UV–Vis spectral comparisons indicate that the aniline modified hydrazone-azomethine dyes show significant red shifts compared with their common full heterocyclic precursor and respective half heterocyclic dyes with the same substituents in the absence of the 2-aminothiophene moiety. The incorporation of CHN and NHN units in the targeting hydrazone-azomethine dyes, which results in the increase of the π -conjugated system, is responsible for the bathochromic shifts in the UV–Vis spectra. Furthermore, solvatochromism and acid-base titration experiments have been carried out to explore the possible proton transfer within the multiple heteroatoms for this family of compounds. Our results demonstrate the existence of an equilibrium between the hydrazone and azo-keto tautomers and the transformation can be driven by the polarity of solvents and pH values. In addition, the easily deprotonated azo-enol tautomer is unlikely to be formed because of the alkaline stability in both organic solvents and water for this series of pyrazolone-based heterocyclic dyes. Graphical abstract: Highlights: A series of pyrazolone-based hydrazone and hydrazone-azomethine dyes is prepared. Hydrazone ⇌ azo-keto transfer is verified by solvatochromism and acid-base titration. Hydrazone-azomethine dyes show significant bathochromic shifts of 27–85 nm. A representative crystal structures for full heterocyclic hydrazone dye is described.